The Evaluation of the Patient Undergoing an Elective Transjugular Intrahepatic Portosystemic Shunt Procedure - Ferral, Hector (Thieme Medical Publishers, 2005)
In its early stages, the transjugular intrahepatic portosystemic shunt (TIPS) was utilized as a lifesaving procedure to treat uncontrollable esophageal variceal bleeding. Most of the initial cases were performed in an emergency situation in the worst possible conditions. The experience gained over the past 15 years has established TIPS as an important therapeutic option in the management of patients with complications of portal hypertension such as variceal bleeding or refractory ascites who do not respond to medical therapy. In current medical practice, 80 to 90% of TIPS procedures are performed in an elective or semielective fashion and only a small percentage of cases are now performed on an emergency basis. The experience gained has demonstrated that certain patients do not benefit from a TIPS procedure and furthermore, their baseline condition may even worsen after a TIPS. This article reviews the most important aspects of the clinical evaluation of patients undergoing an elective TIPS procedure.